Penerapan Sistem Informasi Menggunakan Analisis Value Chain Studi Kasus: PT Intan Pariwara Klaten - Retnowati, Nurcahyani Dewi (Jurnal Buana Informatika, 2011)
Abstract. Implementation of Information Systems Using Value Chain Analysis, Case Study: PT Intan Pariwara Klaten. The business activity of PT Intan Pariwara was begun from acceptance of the text, the process editing or the editing of the text, the provisions of all the elements artistic that was needed in the compilation of the book, to handed over CD file the text was ready printed this to the printing house side. The printing house side will afterwards hand over the book that has been printed to the publisher to afterwards be kept in the warehouse to be carried out by the packing and be ready to be distributed to all delegation all over Indonesia. The business strategy for PT Intan Pariwara was to carry out the marketing with marketing powers that had product knowledge that was high enough but also went through an internet media that could increase the companys turnover. The strategy and information technology of the information system for PT Intan Pariwara that is developing the information system that could bridge the publisher with the customer so as to be known by the consumers wish against products that were produced by the publisher. Keywords: Information System, Value Chain analysis, Business Strategy Abstrak. Aktivitas bisnis PT Intan Pariwara dimulai dengan penerimaan naskah dari penulis kemuadian dilakukan proses editing atau penyuntingan naskah, penyiapan semua elemen artistic yang dibutuhkan dalam penyusunan buku yang meliputi cover buku dan ilustrasi yang berguna untuk memperjelas materi hingga menyerahkan CD file naskah siap cetak tersebut ke pihak percetakan. Pihak percetakan kemudian akan menyerahkan buku yang sudah dicetak ke penerbit untuk kemudian disimpan di gudang untuk dilakukan pengepakan dan siap didistribusikan ke semua perwakilan di seluruh Indonesia. Strategi bisnis PT Intan Pariwara antara lain strategi pengembangan pemasaran melalui internet dan strategi peningkatan hubungannya dengan pelanggan melalui sistem CRM. Sistem atau aplikasi yang perlu dikembangkan antara lain situs interaktif dan CRM (Customer Relationship Management) Kata Kunci: Sistem Informasi, Analisis Value Chain (Rantai Nilai), Strategi Bisnis